Examining the Value of Children in Terms of Family Structure for Families in Northern Cyprus - Eser, Başak; Yazgin, Eda (Pedagogika, 2023)
In order to shed light on the role of children in today’s society, and understand the importance of family relationships, parents are the main instrument, which affects the formation and development of the child, the attitude of the parents to children, helps to more clearly recognize the importance of family relationships. This study investigates the model of the family reflection of today’s family changes the way of the family structure is considered as well. The aim of the study is to examine the values parents attribute to their children with regards to culture and family structures.